Corporate Social Performance as a Determinant of Firm Financial Distress: Insights from the Johannesburg Stock Exchange - Bergstedt, Nasif (Department of Finance and Tax, 2025)
This study examines how Corporate Social Performance (CSP) levels affect the likelihood of firm financial distress in an emerging market context across economic cycles. The significance of this research lies in addressing the gaps in existing literature, which predominantly focuses on mature markets and often overlooks the varying impacts of CSP beyond crisis periods. Using the De la Rey K-score to measure firm Bankruptcy Likelihood (BL) and Thomson Reuters Eikon Refinitiv Environmental, Social and Governance (ESG) scores for CSP assessment, panel regression analysis is conducted on a sample of 321 firmyear observations from non-financial and non-real estate companies listed on the Johannesburg Stock Exchange (JSE) in South Africa over the period 2008 to 2023. The analysis controls for firm leverage, size, profitability, liquidity and time-fixed effects. The key findings are as follows: 1. During upswings, the environmental and social dimensions of CSP do not significantly affect firm BL, aligning with recent research suggesting that high CSP, while fostering loyal stakeholders, may not be crucial when economic conditions are favourable enough to alleviate distress. However, higher aggregated CSP levels increase firm BL, primarily driven by the governance dimension, which is perceived to divert resources and attention from core business operations. 2. Consistent with prior studies, higher social dimension levels of CSP reduces firm BL during downswing periods, emphasising the importance of stakeholder relationships in times of economic instability. In conclusion, bolstering CSP during upswings primarily results in costs, thereby increasing firm BL. However, higher social dimension levels of CSP can mitigate the risk of financial default during subsequent crisis periods. Thus, CSP investments during upswings, although not immediately beneficial, can help balance bankruptcy risk across economic cycles. These findings bear implications for policymakers, corporate management teams, investment practitioners and scholars, offering insights for guiding regulatory efforts, managing firm risk, enhancing investment decisions and future research endeavours.